2015
DOI: 10.1155/2015/729463
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Four Genetic Variants in Han Chinese Subjects with High Myopia

Abstract: High myopia is one of the leading causes of blindness worldwide. However, the exact etiology of high myopia remains unraveled despite numerous attempts of elucidation. Previous genome-wide association study (GWAS) has revealed that four single nucleotide polymorphisms (SNPs), including rs2969180, rs1652333, rs9307551, and rs7837791, were associated with high myopia in Caucasians. The present study was conducted to investigate whether these genetic variants were associated with high myopia in Han Chinese. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…This is consistent with a previous understanding of the relationship between genes and myopia [50]. An increasing number of genes associated with high myopia have been found [51][52][53][54]. In the study of myopia among children and adolescents, the prevalence of high myopia was close to 20% in areas with a high prevalence of myopia [55,56].…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with a previous understanding of the relationship between genes and myopia [50]. An increasing number of genes associated with high myopia have been found [51][52][53][54]. In the study of myopia among children and adolescents, the prevalence of high myopia was close to 20% in areas with a high prevalence of myopia [55,56].…”
Section: Discussionsupporting
confidence: 90%
“…The difference between this study and other studies is that the prevalence of high myopia in boys (3.8%) was higher than that in girls (2.7%), whereas multiple studies have shown that the prevalence of high myopia in girls is higher than that in boys [ 44 – 47 ]. A study [ 48 ] reported that the rs9307551 gene, which is related to high myopia, is highly related to the Han female population. The age range was 6 to 15 years in our study, compared with a large number of studies that reported high myopia rates in older youth (>16 years old); further investigation is needed.…”
Section: Discussionmentioning
confidence: 99%
“…High myopia of genetic etiology tends to be early in onset and severe. Although an increasing number of genes associated with high myopia have been found [57][58][59][60] , previous studies have indicated that the epidemic of high myopia is caused by environmental factors 56 . "Acquired" high myopia is associated with the early onset of myopia because of the early imposition of severe study pressure, which gives myopia more time to progress before it stabilizes 56,61 .…”
Section: Discussionmentioning
confidence: 99%